(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper starts from the assumption of recognising science as potential driving force of the evolution of biolaw. After having clarified the need for a functional connection between scientific and constitutional dimension, the propulsive function of science is analysed with regard to the effective protection of fundamental rights, the impact over the characteristics of the law-making process and constitutional justice.